Multimodal backpacking experience in Finland: Sharing experiences through an online travel blog - Bohjanen, Juhani (HAAGA-HELIA ammattikorkeakoulu, 2015)
Author or authors Juhani Bohjanen Group or year of entry 2011 Title of report Multimodal backpacking experience in Finland: Sharing experiences through an online travel blog Number of pages and appendices 23 + 35 Teacher(s) or supervisor(s) Soile Kallinen Backpacking adventures bring about a whole host of experiences to the individual embarking on such endeavors. With elements such as educational and esthetic realms the backpacker is actively participating and immersing themselves in the overall experience. Which garners a whole host of exciting stories and adventures that are just waiting to be shared with friends and family. The goals of this project based thesis are to define the experience elements of backpacking through existing literature, and put into practice those elements most important to backpacking via hands-on field work, subsequently resulting in a two week backpacking adventure to northern Finland, using multi-modal means of transportation and accommodations. And finally to disseminate the experiences gleaned, by way of an online travel blog, and to create interest in the readers about backpacking adventure in Finland. Implementation began in the winter of 2014 with pre-trip planning, consisting of daily hiking and conditioning, plus gear lists were drawn up. The execution of the actual backpacking journey started June 3rd 2014 and lasted for a length of two weeks. Which consisted of travel via Train, bus, car, and hitchiking. Accomodations included camping, wilderness shelters, hostels, couschsurfing and hotels. During the journey a travel dairy was kept and photographs taken for documentation. Post trip saw the creation of an online travel blog with content of the experiences gained during the field-work. The results demonstrated the elements and dimensions of experiences set forth in the theoretical framework. And the creation of the travel blog proved an invaluable way to share the experiences from the two week backpacking adventure. Furthermore comments received from the target audience were ...